Generation of Human-Like Movement from Symbolized Information - Okajima, Shotaro; Tournier, Maxime; Alnajjar, Fady S.; Hayashibe, Mitsuhiro; Hasegawa, Yasuhisa; Shimoda, Shingo (Frontiers in Neurorobotics, 2018)
An important function missing from current robotic systems is a human-like method for creating behavior from symbolized information. This function could be used to assess the extent to which robotic behavior is human-like because it distinguishes human motion from that of human-made machines created using currently available techniques. The purpose of this research is to clarify the mechanisms that generate automatic motor commands to achieve symbolized behavior. We design a controller with a learning method called tacit learning, which considers system--environment interactions, and a transfer method called mechanical resonance mode, which transfers the control signals into a mechanical resonance mode space(MRM-space). We conduct simulations and experiments that involve standing balance control against disturbances with a two-degree-of-freedom inverted pendulum and bipedal walking control with humanoid robots. In the simulations and experiments on standing balance control, the pendulum can become upright after a disturbance by adjusting a few symbolized signals in MRM-space with tacit learning. In the simulations and experiments on bipedal walking control, the robots realize a wide variety of walking by manually adjusting a few symbolized signals in MRM-space. The results show that transferring the signals to an appropriate control space is the key process for reducing the complexity of the signals from the environment and achieving diverse behavior.